Multi-ethnic GWAS and meta-analysis of sleep quality identify MPP6 as a novel gene that functions in sleep center neurons. Issue 3 (9th October 2020) - Khoury, Samar; Wang, Qiao-Ping; Parisien, Marc; Gris, Pavel; Bortsov, Andrey V; Linnstaedt, Sarah D; McLean, Samuel A; Tungate, Andrew S; Sofer, Tamar; Lee, Jiwon; Louie, Tin; Redline, Susan; et al.
Abstract: Poor sleep quality can have harmful health consequences. Although many aspects of sleep are heritable, the understandings of genetic factors involved in its physiology remain limited. Here, we performed a genome-wide association study (GWAS) using the Pittsburgh Sleep Quality Index (PSQI) in a multi-ethnic discovery cohort ( n = 2868) and found two novel genome-wide loci on chromosomes 2 and 7 associated with global sleep quality. A meta-analysis in 12 independent cohorts (100 000 individuals) replicated the association on chromosome 7 between NPY and MPP6 . While NPY is an important sleep gene, we tested for an independent functional role of MPP6 . Expression data showed an association of this locus with both NPY and MPP6 mRNA levels in brain tissues. Moreover, knockdown of an orthologue of MPP6 in Drosophila melanogaste r sleep center neurons resulted in decreased sleep duration. With convergent evidence, we describe a new locus impacting human variability in sleep quality through known NPY and novel MPP6 sleep genes.